Pelatihan Smart Farming Berbasis IoT Kepada Kelompok Tani Jamur Tiramu Dalam Peningkatan Ekonomi Di Kabupaten Kampar - Rusadi, Sylvina; Hanifah, Anggi; Dewi, Ilma Satriana (Universitas Muhammadiyah Malang, 2023)
Purpose - This community service activity aims to socialize Smart Farming as a new concept in agriculture by integrating technology as an innovation. Smart Farming makes it easy for farmers to increase the quality and quantity of agricultural products through technology. The technology used in this activity is IoT (Internet of Things), a mushroom media sprayer that can be controlled automatically and adjusted to the required temperature. Design/methodology/approach – The methodology used in this community service activity is mentoring and outreach. This activity is a training that concerns two activity themes, namely mentoring the installation of IoT on mushroom media and socializing the business management of oyster mushroom products. Assistance activities will be carried out by technology experts who will guide partners in assembling IoT circuits. In comparison, the socialization that will be carried out will involve resource persons who are experts in agribusiness and will provide debriefing on the management of oyster mushroom input supplies. Findings – Community service activities for Tiramu oyster mushroom partners that are carried out obtain the results of activities that bring significant benefits to partners. The benefit obtained from this activity is an automatic sprayer technology that can be adjusted to the room temperature conditions of the oyster mushroom required by the oyster mushroom. Partners' skills and knowledge also increase with socialization activities that equip partners with knowledge in improving the quality and quantity of oyster mushroom products produced. From some of the things mentioned above, community service activities with results in a series of IoT and partner skills can be said to have enormous benefits for Tiramu oyster mushroom partners. Originality/value – The implications of community service activities produce smart farming technology tools and the ability of Tiramu oyster mushroom partners to improve product quality and quantity.